PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Hiu, Eve Josephine; Maran (ITB AAS Indonesia Surakarta, 2025)
This study seeks to examine how profitability and leverage influence company worth, with dividend policy acting as a moderating factor. This research was conducted using a quantitative approach with panel data regression and Moderated Regression Analysis (MRA) techniques. The population in this study uses industrials companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The sample in this study used a purposive sampling method, the sample obtained was 24 companies that were consistently listed on the IDX in 2019-2024, so that 109 observational data were obtained. Data processing was carried out using EViews 13 software. The analysis results indicate that profitability has a direct (positive) and substantial impact on company value. In the meantime, leverage exerts no notable impact. By incorporating dividend policy as a moderating variable, it was determined that dividend policy can notably enhance (moderate) the connection between profitability and leverage regarding company value, despite the effect's direction being contrary (negative). These results highlight the significance of dividend policy in reinforcing the relationship framework among financial variables and aiding strategic choices to enhance company worth.